Characterization of electron beam generated in ignitor-plasma interaction of shock ignition concept - Somayeh Rezaei; Amirhossein Farahbod; Mohammadjafar Jafari; Samad Sobhanian (مجله علوم و فنون هسته‌ای, 2015)
Generally, laser ignitior parameters in shock ignition concept are above the threshold for laser-plasma instability and therefore are prompting the generation of fast electrons. Depending on the electron energy spectrum and compressed fuel density, the electrons can cause fuel preheating or increase the shock wave amplitude. In this paper, first, the target hydrodynamic parameters are calculated before driving ignitor pulse. Then, electron energy spectrum in the interaction of ignitor with plasma for laser intensity of 1016 Wcm-2 is considered. For density and temperature profiles of the compressed fuel, fluid approach and to evaluate ignitor pulse interaction with plasma, the kinetic approach are adopted. Considering the actual situation of the plasma at the moment of maximum compression, PIC simulations of high-scale, high-temperature and non-homogeneous plasma show bi-Maxwellian electron distribution.